Peran Sistem Informasi Akuntansi dalam Tata Kelola Keuangan di Sektor Publik - Khairani, Suci; Yulanda, Kiki; Sari, Eka Nurmala (Jurnal Riset Akuntansi dan Bisnis, 2025)
The role of accounting information systems (AIS) in public sector financial governance has been a key focus in numerous studies. This research aims to examine the contribution of AIS to transparency, accountability, efficiency, and integrity in public financial management. The method employed is a literature review of relevant empirical studies published between 2021 and 2024. The findings indicate that the consistent implementation of AIS positively impacts the quality of financial governance in government institutions. AIS has been proven to accelerate budget preparation, enhance internal control, and provide digital, audit-ready financial reports. These findings affirm that integrating AIS into public financial systems not only improves administrative efficiency but also strengthens public trust in government financial performance. It is recommended that public institutions expand AIS implementation and enhance human resource capacity to maximize its overall benefits. Keyword : accounting information system, accountability, efficiency, transparency